Biomechanical effects of altered multifidus muscle morphology on cervical spine tissues - Xu, Guangming; Li, Chenxing; Sheng, Zhizhong (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundMuscle fat infiltration and atrophy were common pathomorphologic changes in the paravertebral muscles. Some studies indicated that degeneration of paravertebral muscles may be one of the important causes of chronic neck pain. Therefore, we investigated the mechanical effects of multifidus muscle morphologic changes on cervical spine tissues by constructing cervical spine models of multfiidus muscle with different degrees of atrophy.MethodThree-dimensional finite element models of the cervical spine with 100%, 80%, and 50% with the multifidus muscle were constructed by referring to previous literature. According to the mechanical loading conditions in previous literature, the patient’s head weight and 1 Nm of loading were considered to be applied to the cervical spine, and the mechanical differences in the cervical intervertebral discs, joint capsule, cartilage endplates and range of motion (ROM) due to the morphological changes of the multifidus muscle were recorded and analyzed.ResultUnder anterior flexion loading, model C increasing by 55% and 22% at the C5-6 segment compared to A and B, respectively. Among the three model groups, the stresses in the discs of the lower segments (C4-C7) were significantly higher than those in the upper segments. Under posterior extension loading, the strain values of the joint capsule were higher in the lower cervical segments, with the maximum strain values in the C5-6 segments. The maximum strain values in the lower cartilage endplates were in the C5-6 segments in model group A, whereas the maximum values were in the C4-5 segments in both models B and C. The maximum values in the lower cervical segments were in the C4-6 and C4-5 segments. In addition, a similar trend described above occurs in lateral bending and axial rotation conditions. The ROM of the lower cervical was higher than that of the upper cervical vertebrae, except in lateral bending conditions.ConclusionIn this study, we constructed the morphology of the multifidus muscle to more realistically simulate the mechanical environment of the cervical spine in vivo and quantitatively explored the effects of multifidus muscle atrophy on cervical spine tissues. The results showed that volume atrophy of the multifidus muscle altered the mechanical response of cervical spine tissues. Volume atrophy of the multifidus muscle significantly increased the mechanical indexes of the cervical spine tissues, in which the cervical disc stresses, joint capsule strains, and cartilage endplates increased significantly. Compared with the mechanical changes in the upper cervical segments, the mechanical changes in the lower cervical segments were higher. Therefore, it is important to moderately increase the functional exercise of the multifidus muscle to prevent atrophy leading to abnormal stress concentrations in cervical tissues.